Kinetics of Oxidation of Cobalt(III) Bound and Unbound α-hydroxy Acids by Quinolinium Dichromate - Sankaran, K.R.; Gnanasekaran, K. (Asian Journal of Chemistry, 2010)
Quinolinium dichromate (QDC) oxidizes pentaammine cobalt(III) bound and unbound mandelic and lactic acids, in the presence of 0.50 mol dm-3 HCIO4. The reaction has unit dependence on α-hydroxy acids/cobalt(III) complex and QDC. The comparative study of QDC oxidation of cobalt(III) bound and unbound α-hydroxy acids may throw light on the mechanistic aspects of this reaction.